ANALYSIS OF THE FACTORS CAUSING TO BUDGET DISBURSEMENT AT THE END OF THE BUDGET YEAR (STUDY AT UNIVERSITAS NEGERI SEMARANG) - Nurchayati Nurchayati; Herlina Herlina; Rudi Hartono; Kiswanto Kiswanto (Faculty of Economic and Business Universitas STIKUBANK, 2022)
This study aims to analyze the effect of budget planning, human resource competence, procurement of goods/services and organizational commitment on budget absorption. The approach uses a quantitative approach with the type of data used in this study is quantitative data sourced from primary data. The sample in this study were 99 employees who work at UNNES. The analytical tool used is SmartPLS version 3.3.9. The results showed that budget planning, human resource competence, procurement of goods/services and organizational commitment had a positive effect on budget absorption